MANAJEMEN PERPUSTAKAAN SEKOLAH MENENGAH PERTAMA NEGERI 1 MERANGIN - Sari, Mayang; Nofriana, Rila; Faizzah, Faizzah; Nuzli, Muhammad; Heryanti, Erda (Sosio Akademika, 2022)
This research was conducted to see the important role of libraries in schools to encourage the implementation of the learning process in organizing education which cannot be ignored. Research has been conducted on how library management in Merangin 1 Public Middle School is related to organizational structure, materials or library collections, services, cooperation, and regulations that apply in the library using a qualitative approach in which the data is analyzed using data reduction techniques, data display and data verification. The results of the research carried out that have been fulfilled are the functions of the library, while those related to how to collect/hold information, organizational structure, service and understanding of officers towards library management have not been fulfilled.